2023
DOI: 10.1089/lap.2019.0516
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Pediatric Robot-Assisted Surgery in Italy: Epidemiologic National Survey and Future Directions

Abstract: Background: Pediatric robot-assisted surgery (RAS) is gaining increasing acceptance. We aimed to assess the diffusion of pediatric RAS in Italy, the training period, indications, preliminary outcomes, and limitations. Materials and Methods: An online questionnaire-based survey was performed. The data about robotic activity of 9 Italian Pediatric Surgery units were collected and analyzed. Results: Most of the participating centers (7/9, 77.8%) started RAS less than 5 years ago with only 2 centers (22.2%) perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…Our youngest patient was 7 months old. Of the children under 5 years of age who underwent surgery, The distribution of pathologies reported by other studies (24) shows higher prevalence of urological pathologies, which in our case represented 35%. Digestive/tumor pathologies are overrepresented in our study because minor abdominal procedures such as appendectomy or cholecystectomy have been used as a starting point for robotic surgery programs (25) .…”
Section: Discussionsupporting
confidence: 46%
“…Our youngest patient was 7 months old. Of the children under 5 years of age who underwent surgery, The distribution of pathologies reported by other studies (24) shows higher prevalence of urological pathologies, which in our case represented 35%. Digestive/tumor pathologies are overrepresented in our study because minor abdominal procedures such as appendectomy or cholecystectomy have been used as a starting point for robotic surgery programs (25) .…”
Section: Discussionsupporting
confidence: 46%
“…17 To date, a recent Italian survey reported that pyeloplasty was the most frequent RALS procedure performed in the Units of Pediatric Surgery. 18 Conversely, RALS extravesical ureteral reimplantation has not already reach the same standards of success of the open surgery, showing a higher rate of complications. 19 However, RALS presented higher costs, a learning-curve for the operators, and the need of a dedicated setting and surgical team.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the current hardware equipment and the characteristics of pediatric surgical diseases. Current authors recognize that robotic surgery is safe in children with a body weight of more than 15 kilograms and aged more than 2 years [8] . Our patient was 12 years old and weighed 41 kilograms, which is still widely recognized as eligible for robotic surgery.…”
Section: Resultsmentioning
confidence: 99%